Scientific production on extension in Latin American higher education: a systematic literature review - Matos Pegoraro, Seris de Oliveira (2026)
This article presents a systematic literature review, qualitative, about the scientific production on extension in higher education in the Latin American context (SciELO, January 2015 to July 2024), with the objective of outlining an overview of this and identifying how extension has been interpreted and implemented. From 2,790 initial records, after exclusion of duplicates (n=1,200) and screening (n=466), a predominance of experience reports was found, indicating an eminently practical character attributed to extension, despite the growing academic interest. For in-depth analysis, a corpus of nine articles was selected with an explicit focus on extension as an object of study and direct empirical data with its agents, such as students, teachers, administrators, and the external community. The characterization of this corpus revealed studies that were mostly from public universities, qualitative, and focused on the academic community, and indicated a field that still faces challenges in terms of funding and specialized research in the area. The discursive textual analysis resulted in two final categories: purpose of extension and development of extension. Regarding the purpose, expressed in social commitment and academic training, a heterogeneity of meanings and practices emerged, with a predominance of more instrumental and diffusionist conceptions. Regarding its development, it was observed a trend of management processes oriented towards quality and impact measurement. Furthermore, despite the persistent strength of the ideals of the University Reform of 1918, the analysis indicates a cycle of disrepute of extension, evidenced by low institutional support, challenges in motivating teachers and students, reduced qualified scientific production on the topic and scarce funding, impacting the achievement of the university's transformative social mission in the region.